Prototyping and usability testing of a metadata schema creation and selection module for OpenBiblio - Kangleon, Ebony R.; Torralba, Christienne Mikhaille C. (2012)
The development via customization of existing integrated library systems (ILS) is not an unfamiliar thesis topic, especially in the UP School of Library and Information Studies (UP SLIS). Numerous studies have been conducted on the various stages of the development: analysis, design, prototype, usability, implementation, and evaluation. However, most of these are concerned with a specific institution; very few intended their studies to be adaptable to other institutions which may or may not share the same library policies. With this in mind, the study focused on developing a prototype and conducting a usability test for a metadata schema selection and creation module for OpenBiblio that is targeted towards special libraries and institutions. This research partially adapted a previously proposed design as its basis for the module from the undergraduate thesis, Design of an Integrated Library System with Metadata Schema Creation and Selection through Entity Relationship Modeling of Selected Special Libraries in Metro Manila by Santillan (2010), with minor modifications as seen by the researchers. Agile methodology was used in planning, structuring and prototyping the system. Three metadata modules were added to OpenBiblio, namely, Metadata Object Description Schema (MODS), a combination of Simple Dublin Core (SDC of simply DC) and an application profile of Dublin core called Dublin Core Education (DC-ED), and lastly, a combination of the Categories of the Description Works of Art (CDWA) and Cataloging Cultural Objects (CCO).